Cash-out vs. cash-in refinancings: their dynamic relationships with stock market and real estate factors. (24th November 2010) - He, Ling T.; Casey, K. Michael
This study addresses the relationship between cash-out and cash-in mortgage refinancings and the stock market. Liquefying home equity is the major reason for the cash-out refinancings, whereas the cash-in refinancings are primarily for an earlier mortgage payoff. This study analyses responses of each type of refinancing to innovations in the stock market, mortgage rates, effective maturity and home appreciation rates and the relative importance of these innovations to refinancing activities using orthogonalised impulse response and variance decomposition matrixes from vector autoregression. We find that changes in stock prices do appear to impact mortgage refinancing decisions.